A Theoretical Analysis of Real Estate Returns - FOGLER, H. RUSSELL; GRANITO, MICHAEL R.; SMITH, LAURENCE R. (Journal of Finance, 1985)
ABSTRACT In this paper, we consider two hypotheses for the recent performance of real estate returns. The first is the random event argument that real estate is positively correlated with unanticipated inflation but that structural change in expected returns due to a change in the perceived sensitivity of returns to unanticipated inflation has not taken place. The second is the hedge demand argument that formulates the structural shift hypothesis. The paucity of real estate and other expectations data as well as the general identification problem make it extremely difficult to distinguish between these hypothesis. Our tests consist of estimates of inflation betas for various asset categories overtime as well as estimates of the hedge vector, . Although some support for the hedge argument is found, the results are not strong enough to reject the random event argument and conclude that a decline in the required return on real estate due to a relative increase in inflation beta drove returns during the 1970's.